The Regulation of Diversion in Indonesia’s Juvenile Criminal Justice System Oriented Toward the Best Interests of the Child And Fairness - Walim, Walim; Santoso, M. Iman; Haryono, Waty Suwarty; Marbun, Rocky (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
Background. Children in conflict with the law require special protection, and diversion is a mechanism designed to shift the resolution of juvenile cases from the criminal justice process to alternative, non-judicial measures. In Indonesia, the implementation of diversion under Law No. 11 of 2012 has not yet been fully optimized, with law enforcement, prosecution, and courts often prioritizing imprisonment as the primary response. This approach fails to serve the best interests of the child, as the current diversion regulations limit its application to specific offenses. Purpose. This study identifies several issues, including the practical implementation of diversion within Indonesia's juvenile justice system, why the current diversion rules are not fully oriented toward the child's best interests, and how these regulations have improved. Method. The research employs a normative legal method with an empirical juridical approach. Result. The findings indicate that although Law No. 11 of 2012 substantively regulates diversion and promotes restorative justice, there are still weaknesses in the legal substance, legal system, and legal culture. Reform is necessary to address these shortcomings, taking into account sociological, philosophical, and psychological perspectives. Changes to the diversion regulations should include all juvenile offenses without limitation and ensure that diversion is oriented toward the best interests of the child while incorporating principles of justice for victims, including compensation and the restoration of relationships between victims and offenders, by Article 1320 of the Indonesian Civil Code. Conclusion. Indonesia's Juvenile Criminal Justice System, under Law Number 11 of 2012, aims for non-punitive measures but struggles with limited implementation due to legal structure and practice issues. To enhance the system, Article 7, paragraph (2), letter (a) should be amended to allow diversion for all juvenile offenses, reflecting principles from the Convention on the Rights of the Child and restorative justice. If diversion fails, the judicial process can proceed as per existing laws.